Two-dimensional semiconductors in the regime of strong light-matter coupling - Christian Schneider (Nature Portfolio, 2018)
Excitons, quasi-particles of tightly bound electron-hole pairs, dominate the optical response of atomically thin transition metal dichalcogenides. Here, the authors review strong light-matter coupling in two-dimensional semiconductors arising from confined excitons interacting with trapped photons or localized plasmons.